The Significance of Exposure to Pregestational Type 2 Diabetes in Utero on Fetal Renal Size and Subcutaneous Fat Thickness. (30th June 2022) - Pylypjuk, Christy L.; Day, Chelsea; ElSalakawy, Yasmine; Reid, Gregory J.
Abstract : Objectives . To determine the relationship between exposure to pregestational type 2 diabetes (T2D) and renal size and subcutaneous fat thickness in fetuses during routine obstetrical ultrasound. Methods . This was a case-control study (January 1, 2019 to December 31, 2019). Routine obstetrical ultrasounds performed between 18 and 22 weeks' gestation at a tertiary-care fetal assessment unit were reviewed. "Cases" comprised ultrasounds of fetuses exposed to pregestational T2D in utero. The control group was assembled from ultrasounds of healthy controls. Postprocessing measurements of fetal renal size and abdominal wall thickness from stored images were performed by two independent observers, and findings were compared between groups. Results . There were 54 cases and 428 ultrasounds of healthy controls. The mean maternal age of cases was 32.1 years (SD 6.2) compared to 33.2 years (SD 5.3) for healthy controls, and the majority of ultrasounds were performed in multiparous patients (83%). At the 18 to 22 week ultrasound, there was a significant reduction in renal size amongst fetuses exposed to maternal T2D in utero compared to controls; among cases, the mean renal width was 8.0 mm (95% CI 7.8–8.1) compared to 11.4 mm (95% CI 10.6–12.7) in controls (p < 0.0001 ); the mean renal thickness among cases was 8.1 mm (95% CI 7.9–8.2) compared to 11.5 mm (95% CI 10.7–12.9) in controls (p = 0.001 ). There was no obvious difference in estimated fetal weight between groups, yet fetuses exposed to maternal T2D had increased subcutaneous abdominal wall fat thickness at this early gestational age (p = 0.008 ). Conclusions . Fetal renal size in cases exposed to pregestational T2D is significantly smaller compared to controls, and subcutaneous abdominal wall fat is significantly thicker. Given emerging evidence about the developmental origins of disease, further study is needed to correlate the association between fetal renal size and fat distribution in the fetus and the long-term risk of chronic renal disease and diabetes in these offspring.